Teacher’s perceptions and barriers to employing cooperative learning strategies in rural secondary classrooms using the English language / Wan Norul Addinie Mohd Naser - Mohd Naser, Wan Norul Addinie (2011)
This study is mainly to investigate Teacher’s Perceptions and Barriers to Employing Cooperative Learning in rural Secondary Classrooms using English Language. Although there are many researches regarding Cooperative Learning but most of them did not focus in rural areas. The purpose of this study is to investigate Teacher’s perceptions and awareness towards the implementation of Cooperative Learning Strategies in rural Secondary Classrooms using English Language. Beside, this study is to identify whether Cooperative Learning is applicable to be implemented in rural secondary classrooms using English Language. And lastly, to find out what are the barriers and challenges faced by teachers towards the implementation of Cooperative Learning Strategies in rural Secondary Classrooms using English Language. The findings support that Cooperative Learning should be implemented in rural Secondary Classrooms using English language because it is beneficial to the teachers as well as the students.